Labour Mobility in German Establishments during the COVID-19 Crisis: Panel Data Analyses with Special Reference to Short-Time Work and Working from Home - Lisa Bellmann; Lutz Bellmann; Olaf Hübler (Institute of Labor Economics (IZA), 2023)
Using 21 waves of German high-frequency establishment panel data collected during the COVID-19 crisis, we investigate the effects of short-time work (STW) and working from home (WFH) on hiring, firings, resignations and excess labour turnover (or churning). Thus, we enquire whether STW avoids firings as intended by policymakers and is associated with unintended side effects by subsidising some establishments and locking in some employees. Additionally, where it was feasible, establishments used WFH to continue working without risking an increase in COVID-19 infections and allowing employed parents to care for children attending closed schools. While much of the literature investigating the effects of STW and WFH remains descriptive, we conduct panel data analyses. We apply data and methods that allow for the dynamic pattern of STW and WFH during the pandemic. Furthermore, our data include relevant establishment-level variables, such as the existence of a works council, employee qualifications, establishment size, the degree to which the establishment was affected by the COVID-19 crisis, industry affiliation and a wave indicator for the period the survey was conducted. Our results show the important influences of STW and WFH on employment during the pandemic. By means of STW, establishments are able to avoid an increase in involuntary layoffs, and hiring decreases significantly. In contrast, WFH is associated with a rise in resignations.
Keywords: C23; J21; J23; J58; J63; 330; short-time work; working from home; labour mobility; COVID-19; panel analysis; high-frequency establishment data